Colorado Pediatric Airway Score (COPUR) as a Predictor of Intubation Difficulty in Children Aged 1-8 Years - Kapuangan, Christopher; Perdana, Aries; Fadhila, Fulki; Ramlan, Andi Ade Wijaya; Zahra, Raihanita; Ferdiana, Komang Ayu; Rahendra, Rahendra (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Airway management is critical in pediatric anesthesia, as failure can lead to severe complications, including cardiac arrest. Anticipating and preparing for difficult intubation is essential, particularly in children with unique anatomical and physiological characteristics. The Colorado Pediatric Airway Score (COPUR) is a predictive tool for assessing intubation difficulty in pediatric patients.Objective: This study evaluates the validity of COPUR in predicting difficult intubation in children.Methods: A cross-sectional diagnostic study was conducted on 121 pediatric patients (aged 1–8 years) undergoing general anesthesia at Cipto Mangunkusumo Hospital. COPUR assesses jaw structure, mouth opening, prior intubation history, uvula visibility, neck movement, and additional modifying factors (macroglossia, obesity, mucopolysaccharidosis, and protruding teeth). A COPUR score >7 was used to predict difficult intubation, while intubation difficulty was defined by an Intubation Difficulty Score (IDS) >5.Results: A COPUR score ≥8 predicted difficult intubation in 15.7% of patients, whereas actual difficult intubation occurred in 9.92%. A COPUR threshold of ≥7 provided optimal sensitivity (83.3%) and specificity (61.47%), outperforming the original cutoff of 8 (50% sensitivity, 87% specificity). The score demonstrated good discriminative ability (AUC-ROC: 0.770, 95% CI: 0.685–0.842) and suitable calibration (Hosmer-Lemeshow test, p = 0.584).Conclusion: The COPUR score is a valid tool for predicting difficult intubation in pediatric patients aged 1–8 years, demonstrating fairly good discrimination and calibration values.